Evolution of regulatory mechanisms underlying nutrition-responsive plasticity in insects - Casasa, Sofia (Frontiers in Ecology and Evolution, 2024)
Phenotypic plasticity is a fundamental property of developing organisms and is thought to play an important role in diversification. Plastic responses themselves are remarkably diverse and respond to a wide range of environmental factors. Here I focus on plasticity in response to variation in nutrition in insects since 1) nutrition is a widespread factor that impacts most organisms, and 2) insects are important models to study phenotypic plasticity. First, I provide a brief overview of our current mechanistic understanding of the regulation of nutritionally cued plasticity in insects, in both traditional as well as emerging model systems. Then, I explore evolutionary mechanisms enabling the diversification of regulation across taxa, emphasizing the role of gene duplication and gene regulatory network co-option. Furthermore, I examine nutrition-responsive phenotypes as suites of multiple traits that develop in a coordinated manner. I argue that understanding how these traits are integrated at the molecular level can shed light on the evolution of complex phenotypes. Finally, I discuss potential challenges and opportunities to further our understanding of nutrition-responsive plasticity, its regulation, and its evolution.